The autonomy of the student of higher education at a distance: In the discipline of methodology of teaching in higher education - Rost , Elton (Seven Editora, 2023)
In this work we seek to discuss and present some issues related to the autonomy of higher education students in the distance learning modality. We begin our discussion seeking to identify and characterize some of the factors that may impair the autonomy of students in their education, and then investigate the aspects that can contribute to motivate, stimulate and strengthen the autonomy of students, both for learning and research, as well as in their continuing education. DOI:https://doi.org/10.56238/ptoketheeducati-015